POLITICAL CONFIGURATION AND LEGAL PRODUCTS IN INDONESIA IN TERMS OF ISLAMIC CONSTITUTIONAL LAW - Ummu Awaliah; Muhammad Saleh Ridwan; Rahmiati Rahmiati; Kusnadi Umar (Universitas Islam Negeri Alauddin Makassar, 2021)
Politics and the state are inseparable. The confusion of the form of politics or what is known as the Political Configuration and Legal Products in Indonesia makes people wonder. Then, Islamic Constitutional Law will look at or see how Indonesia's forms of politics and legal products are used. This study aimed to determine Indonesia's political configuration and legal products in terms of Islamic constitutional law. The type of study was normative legal research or research library. The primary data sources were obtained from Al-Qur'an and Hadith, while the secondary data were obtained from books, journals, or materials taken from writings related to the subject matter. The data collection technique was used through the literature by searching, reading, studying, and reviewing related literature. The results of this study showed that: 1) Indonesia currently used a democratic political configuration and responsive legal products, where the public was given space to express themselves and play an active role in determining policies in the government; 2) Islamic constitutional law considered that the political configuration and legal products in Indonesia were in accordance with what was contained in the Islamic constitutional law. This was because Indonesia's democratic political configuration and legal products had the same vision, namely creating prosperity for the general public.